Clarke, The Countess: The Scandalous Life of Frances Villiers, Countess of Jersey (Amberley Publishing, 2016) - Natalie Hanley-Smith (Royal Studies Journal, 2017)
Review of Tim Clarke, The Countess: The Scandalous Life of Frances Villiers, Countess of Jersey (Gloucestershire: Amberley Publishing, 2016).